Sulfite reductase defines a newly discovered bottleneck for assimilatory sulfate reduction and is essential for growth and development in Arabidopsis thaliana - Khan, Muhammad Sayyar; Haas, Florian Heinrich; Samami, Arman Allboje; Meyer, Andreas; Wirtz, Markus; Hell, Rüdiger (The plant cell, 2010)
The role of sulfite reductase (SiR) in assimilatory reduction of inorganic sulfate to sulfide has long been regarded as insignificant for control of flux in this pathway. Two independent Arabidopsis thaliana T-DNA insertion lines (sir1-1 and sir1-2), each with an insertion in the promoter region of SiR, were isolated. sir1-2 seedlings had 14% SiR transcript levels compared with the wild type and were early seedling lethal. sir1-1 seedlings had 44% SiR transcript levels and were viable but strongly retarded in growth. In mature leaves of sir1-1 plants, the levels of SiR transcript, protein, and enzymatic activity ranged between 17 and 28% compared with the wild type. The 28-fold decrease of incorporation of 35S label into Cys, glutathione, and protein in sir1-1 showed that the decreased activity of SiR generated a severe bottleneck in the assimilatory sulfate reduction pathway. Root sulfate uptake was strongly enhanced, and steady state levels of most of the sulfur-related metabolites, as well as the expression of many primary metabolism genes, were changed in leaves of sir1-1. Hexose and starch contents were decreased, while free amino acids increased. Inorganic carbon, nitrogen, and sulfur composition was also severely altered, demonstrating strong perturbations in metabolism that differed markedly from known sulfate deficiency responses. The results support that SiR is the only gene with this function in the Arabidopsis genome, that optimal activity of SiR is essential for normal growth, and that its downregulation causes severe adaptive reactions of primary and secondary metabolism. Enlargement and doming of the shoot apical meristem (SAM) is a hallmark of the transition from vegetative growth to flowering. While this change is widespread, its role in the flowering process is unknown. The late termination (ltm) tomato (Solanum lycopersicum) mutant shows severely delayed flowering and precocious doming of the vegetative SAM. LTM encodes a kelch domain-containing protein, with no link to known meristem maintenance or flowering time pathways. LTM interacts with the TOPLESS corepressor and with several transcription factors that can provide specificity for its functions. A subgroup of flowering-associated genes is precociously upregulated in vegetative stages of ltm SAMs, among them, the antiflorigen gene SELF PRUNING (SP). A mutation in SP restored the structure of vegetative SAMs in ltm sp double mutants, and late flowering was partially suppressed, suggesting that LTM functions to suppress SP in the vegetative SAM. In agreement, SP-overexpressing wild-type plants exhibited precocious doming of vegetative SAMs combined with late flowering, as found in ltm plants. Strong flowering signals can result in termination of the SAM, usually by its differentiation into a flower. We propose that activation of a floral antagonist that promotes SAM growth in concert with floral transition protects it from such terminating effects.